Evaluation of Chitosan Activity Produced Via Biotransformation of Chitin Against Some Pathogens Associated with Burn Infection in Vitro and in Vivo - Monaam, Zaedoon; Luti, Khalid Jaber kadhum (Iraqi Journal of Science, 2024)
Burn infections are a serious concern for patients with burn injuries, as they can lead to significant morbidity and mortality. The present study was designed to evaluate the chitosan activity against five pathogens collected from burn infections (Escherichia coli ZE15, Acinetobacter bummani ZA2, Klebsiella pneumonia ZK3 and Pseudomonas aeruginosa ZP17, Staphylococcus aureus ZS2). Chitosan was produced in solid-state fermentation using corn meal supplemented with 2% of shrimp shell chitin. The degree of deacetylation of chitosan was 79.5% and the FT-IR spectrum (4000 to 400) cm-1 gave IR spectra similar to that of the commercial chitosan. The produced chitosan showed a significant inhibitory ability from the concentration of 10 mg/ml to 2 mg/ml. The M.I.C. and S.I.C were varied between the isolates; for P. aeruginosa ZP17 and Staph. aureus ZS2, the M.I.C and S.I.C were 1.6 mg/ml and of 1.4 mg/ml respectively, while for E. coli ZE15, Kl. pneumonia ZK3 and A. bumannii ZA2 were 1.4 mg/ml and 1.2 mg/ml. Furthermore, this study showed an the important role of the produced chitosan as an antibiofilm agent to reduce the biofilm formation for the tested isolates. However, the strongest antibiofilm activity was against E. coli Z.E15 with 55.2%. Moreover, four potential formulas containing chitosan with concentration of 1.6 mg/ml were tested. A formula containing polyvinyl alcohol, vaseline and chitosan to create a cream showed the best results in comparison with the four-formula used in this study. This formula was added to pads of thick cellulosic filter paper to treat a mouse model with full thickness cutaneous burn to assess the benefits of treating with a chitosan dressing. The healing process was examined and results showed a signs of remodeling stage by day four and a scar tissue formation by day nine.